Magnesium foliar supplementation increases grain yield of soybean and maize by improving photosynthetic carbon metabolism and antioxidant metabolism - Rodrigues, Vitor Alves [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Bossolani, João William [UNESP]; Moretti, Luiz Gustavo [UNESP]; Portugal, José Roberto [UNESP]; Mundt, Tamara Thaís [UNESP]; de Oliveira, Sirlene Lopes [UNESP]; Garcia, Ariani [UNESP]; Calonego, Juliano Carlos [UNESP]; Lollato, Romulo Pisa (MDPI, 2021)
(1) Background: The aim of this study was to explore whether supplementary magnesium (Mg) foliar fertilization to soybean and maize crops established in a soil without Mg limitation can improve the gas exchange and Rubisco activity, as well as improve antioxidant metabolism, converting higher plant metabolism into grain yield. (2) Methods: Here, we tested foliar Mg supplementation in soybean followed by maize. Nutritional status of plants, photosynthesis, PEPcase and Rubisco activity, sugar concentration on leaves, oxidative stress, antioxidant metabolism, and finally the crops grain yields were determined. (3) Results: Our results demonstrated that foliar Mg supplementation increased the net photosynthetic rate and stomatal conductance, and reduced the sub-stomatal CO2 concentration and leaf transpiration by measuring in light-saturated conditions. The improvement in photosynthesis (gas exchange and Rubisco activity) lead to an increase in the concentration of sugar in the leaves before grain filling. In addition, we also confirmed that foliar Mg fertilization can improve anti-oxidant metabolism, thereby reducing the environmental stress that plants face during their crop cycle in tropical field conditions. (4) Conclusions: Our research brings the new glimpse of foliar Mg fertilization as a strategy to increase the metabolism of crops, resulting in increased grain yields. This type of biological strategy could be encouraged for wide utilization in cropping systems.
Keywords: Carbohydrate partitioning; Foliar application; Oxidative stress; Photosynthesis; Sink-source relationship